Model-based Customer-Relationship Management System and Strategic Board Game: Analogical Training - Lee, Chien Sing *; Ng, Chun Heng; Lee, Jing Sze; Ngo, Kee Xian; Teh, Shin Mae; Akmal, bin Mohamed Ikraam; Lim, Chze Yee; Pandey, Satvik Shahshi (The Institute of Electrical and Electronics Engineers, Inc., 2021)
The pandemic has caused much mental, social and financial stress. Policies and standard operating procedures have helped to alleviate some stress and create systematicity, expectancy, and predictability. This paper aims to alleviate some of the stress through model-based social customer relationship management system, an Augmented Reality board game, and two mini tourism games. The first aims to increase collaboration among stakeholders and to increase more effective and efficient resource management. The second phases players through the preparation, recruitment, attack and observation phases at a slower pace than competitive gaming. The third and fourth project introduce places and trigger memories through mini games respectively. These provide analogical training in social customer relationship management and in developing more systematic thinking, expectations, fun and mindfulness. AI-assistance would enable personalization/intelligent context-aware recommendations.